A roller-coaster ride: Introduction of pentavalent vaccine in India - Harish Nair; Indrajit Hazarika; Ashok Patwari (Edinburgh University Global Health Society, 2011)
Petitioners in High Court cite low disease burden due to Hib and safety concerns as main reasons for opposing the introduction of the vaccine.